2016
DOI: 10.1002/pi.5070
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and physical properties of functionalized graphene/waterborne polyurethane UV-curing composites by click chemistry

Abstract: Functionalized graphene nanoplatelets (f-GNS) were modified with (3-mercaptopropyl)trimethoxysilane (MPTMS) to enhance their compatibility with the polyurethane coating matrix. The results of Fourier transform infrared spectroscopy, AFM, Raman and XRD showed that the MPTMS was successfully attached onto the surface of the graphene nanoplatelets. Functionalized graphene/waterborne polyurethane acrylate (f-GNS/WPUA) nanocomposites were fabricated by UV-curing technology. The SEM and TEM images indicated that f-G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 41 publications
(53 reference statements)
1
13
0
Order By: Relevance
“…The modification of GO with isophore diidocyanate (IPDI) and octadecylamine (ODA) [23], titane coupling agent [24], 3-aminopropyl triethoxysilane (APTES) [25,26], and hydramines (MEA-monorthanolamine, DEA-diethanolamine and TEA-triethylamine) [27] has been reported to improve the compatibly with a WPU matrix. The applications of graphene (pristine, oxidized, or functionalized)/WPU composites as electromagnetic interference (EMI) shielding devices [28][29][30][31][32], textiles [33,34], anticorrosives [24,[35][36][37][38], and flame retardant coatings [39] have also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The modification of GO with isophore diidocyanate (IPDI) and octadecylamine (ODA) [23], titane coupling agent [24], 3-aminopropyl triethoxysilane (APTES) [25,26], and hydramines (MEA-monorthanolamine, DEA-diethanolamine and TEA-triethylamine) [27] has been reported to improve the compatibly with a WPU matrix. The applications of graphene (pristine, oxidized, or functionalized)/WPU composites as electromagnetic interference (EMI) shielding devices [28][29][30][31][32], textiles [33,34], anticorrosives [24,[35][36][37][38], and flame retardant coatings [39] have also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates clearly that the effect of GO on the final epoxy conversion depends on GO content and therefore has to be understood well. The effect of fillers on the UV curing phenomena of the resins has been investigated in several studies with a diversity of reasons suggested for the observations. The decrease of final epoxy conversion has been proposed to be due to either a free‐volume decrease or vitrification of the on‐cure resin .…”
Section: Resultsmentioning
confidence: 99%
“…The decrease of the mechanical properties above a certain GO content was observed in many studies 26,27) . In many studies 13,18,19,28,29) , the incorporation of GO or functionalized graphene results in the decreased EB. Thus, it is meaningful that both stiffness and toughness increase with the incorporation of GO nanosheets in this study.…”
Section: Resultsmentioning
confidence: 99%